Purification and characterization of a new alkaline serine protease from the thermophilic fungus Myceliophthora sp. - Zanphorlin, L. M. [UNESP]; Cabral, Hamilton [UNESP]; Arantes, E.; Assis, D.; Juliano, L.; Juliano, M. A.; Silva, R. [UNESP]; Gomes, E. [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Elsevier B.V., 2011)
This work reports the purification of a novel alkaline protease enzyme from a putative new thermophilic fungus Myceliophthora sp. The molecular weight of the enzyme was determined as 28.2 kDa by using MALDI-TOF MS and it was inhibited by PMSF indicating it is a serine-protease. The optimum pH and temperature were 9.0 and 40-45 degrees C, respectively. Mg was the only tested cation able to promote an increase of the protease activity. The N-terminal sequence of the purified protease (GVVGVC) presented identity and homology when compared to other proteases from fungi. This study also provides biochemical information about substrate specificity using fluorescence resonance energy transfer (FRET) peptide families derived from Abz-KLRSSKQ-EDDnp. The results showed that Abz-KLISSKQ-EDDnp is the best substrate among those tested for the purified protease (k(cat)/K-m = 1275.3 mM(-1)s(-1)). Also, the specificity data suggest that subsites S-1, S-2, S-3 and S-1', S-2', S-3', in general, present a preference for hydrophobic residues with the exception of Glu in P-3. His in P-2' and Arg in P-3'. The highest values for the specificity constant k(cat)/K-m were obtained for P-1, P-2 and P-2'. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Thermophilic fungus; Myceliophthora sp.; Enzyme; Protease; Serine-protease; Fluorescent peptides; Subsite mapping